La prise en compte du cheminement spirituel du jeune selon une perspective d’éducation relative à l’environnement : la problématique québécoise - Virginie Boelen (Éducation et Socialisation)
Despite the wish to consider the children’s spirituality in secular education, Quebec makes part of those countries in which there is a gap between theory and actual classroom practice. The reasons of this situation invite us to reexplore the concept of spirituality. Following its different characteristics and in a context of environmental crisis, we expose the potential of developing an educational model that foster children’s spirituality in a context of environmental education. This model answer to an international worry about living together including all the inhabitants of our unique and suffering world. The final aim of this educational model is to develop a spiritual relational consciousness to the world following an ethic of reliance that promote our sense of responsibility and engage an eco-civic way of being and acting.